ICT and SMEs’ competitiveness in South Africa : how SMEs could use ICT to become competitive in South Africa - Kroeze, J.H. (Jan Hendrik) (University of Pretoria, 2013)
Dissertation (MIT)--University of Pretoria, 2008.